DENOTATIVE AND CONNOTATIVE MEANING IN THE SENTENCE OF “YOU GOT ME FEELING LIKE A PSYCHO” AS THE LINE OF RED VELVET SONG LYRIC - Kharisma Dinata Jakautama; Muhammad Rayhan Bustam (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2022)
The research with the title as ‘Dennotative and Connotative Meaning in the Sentence of “You got me feeling like a psycho” as The Line of Red Velvet Song Lyric’ uses data taken from a song